2009
DOI: 10.1007/s11999-008-0663-z
|View full text |Cite
|
Sign up to set email alerts
|

Case Reports: Lengthening of a Vascularized Free Fibular Graft

Abstract: Wide bone resection is sometimes necessary for bone tumors, and reconstruction is a major challenge. Vascularized fibular graft is one alternative but may result in progressive limb-length discrepancy (LLD) in children with substantial growth left. Progressive distraction lengthening with an external fixator is now a standard procedure to generally correct LLD. However, lengthening of free vascularized fibular grafts for lower limb reconstruction has not been reported frequently and then only in small series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…De Boer and Wood [34] suggested that 80% hypertrophy of the FVFG should be observed at the 2-year’ follow-up. Courvoisier A et al reported that three years after the FVFG seems to be a safe delay [32]. In their study, the mean age of their patients at surgery was 12 years, and the mean interval between the end of reconstruction and lengthening was 10 years.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…De Boer and Wood [34] suggested that 80% hypertrophy of the FVFG should be observed at the 2-year’ follow-up. Courvoisier A et al reported that three years after the FVFG seems to be a safe delay [32]. In their study, the mean age of their patients at surgery was 12 years, and the mean interval between the end of reconstruction and lengthening was 10 years.…”
Section: Discussionmentioning
confidence: 90%
“…There are no guidelines for the lengthening procedure of a FVFG and various types of fixators have been used for bone lengthening. Some authors suggest that fibular graft lengthening using an external fixator is a safe and effective method for correcting LLD [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations